Effect of soil tillage on diversity and relative abundance of macrofungi associated with chestnut in the northeast of Portugal - Baptista, Paula (2011)
European chestnut (Castanea sativa Mill.) is a forest tree of great economic interest for wood and fruit production in the north east of Portugal. In order to maintain the soil free of weeds farmers traditionally practice several superficial tillages along the year. Phytossanitary problems mainly related with increasing Phytophtora cinamomi contamination of soils are progressively changing these practices. The present work intend to evaluate the effect of two different soil management (tillage vs. non tillage) of chestnut orchards on the macrofungi diversity and relative abundance. Two Castanea sativa orchards were selected (one tilled and one non tilled) and five plots of 100m2 each were delimited for macrofungi harvesting. During Autumn – Winter of 2003, all mycorrhizal and nonmycorrhizal mushrooms were collected weekly. Identification and quantification of the number of carpophores per species were made in order to evaluate biodiversity and relative abundance of the species. 50 species of macrofungi belonging to 20 genera were identified. Tillage effect could be realized in terms of the number of species. 17 species from 12 genera were harvested in tilled soils, mainly from the genera Russula, Macrolepiota, Laccaria and Inocybe. Non-tilled soils showed higher number of species (47) and genera (17) and the greater number of species were from the genera Russula, Inocybe, Cortinarius, Tricholoma and Laccaria. From the preliminary results here presented we can say that the soil management practices significantly influence the total number of species and the number of mycorrhizal and nonmycorrhizal mushrooms in chestnut orchards.